2018
DOI: 10.23919/tems.2018.8326455
|View full text |Cite
|
Sign up to set email alerts
|

Modularity techniques in high performance permanent magnet machines and applications

Abstract: This paper reviews the modularity techniques in the stator manufacture of permanent magnet machines for different applications. Some basic concepts of modular machines are firstly introduced. Modular machines for several typical applications are then described in details, including domestic appliances, automobiles and electric vehicles, more electric aircrafts and civic applications, wind power generators, etc. Besides, the influence of manufacture tolerance gaps and flux barriers on the electromagnetic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 50 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Consequently, P pm the level of PMaSnyRMs is quite higher than those of other machine types. Comparison of rated output power P out , expressed in (12) where T e electromagnetic torque and ω r angular speed, for each machine topology is given in Table 4. Moreover, the efficiency η, calculated as expressed in (13), is shown in Fig.…”
Section: Power Losses and Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, P pm the level of PMaSnyRMs is quite higher than those of other machine types. Comparison of rated output power P out , expressed in (12) where T e electromagnetic torque and ω r angular speed, for each machine topology is given in Table 4. Moreover, the efficiency η, calculated as expressed in (13), is shown in Fig.…”
Section: Power Losses and Efficiencymentioning
confidence: 99%
“…In the existing literature, several different studies on reviewing/ comparing the electromagnetic performance characteristics of different machine technologies can be found [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Different electric machine topologies have been compared and it is concluded that the PM machines, particularly having IPM topologies, are one of the best rotor topologies suitable for the electric vehicle (EV)/hybrid electric vehicle (HEV) and aerospace applications [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a common challenge is the complex mechanical support needed for holding each module, no matter it is a joint or a bracket. Nevertheless, [21] had thoroughly reviewed the techniques of modular designs, so there is no need for repeated narrative.…”
Section: Magnet Powder Reusingmentioning
confidence: 99%
“…Considering the demand for electrification of automotive and aerospace traction systems, improving the machine performance is of great significance in terms of the national economy and efficient use of energy sources. For over a decade, great efforts have been made in research and the performance improvement of the electrical machines [7–38]. Some of these studies have been categorised as follows.…”
Section: Introductionmentioning
confidence: 99%